Will Research into the History of Cities Change our Hypotheses Concerning Late Antiquity? (A Review Article) - Wilczyński, Marek (Polskie Towarzystwo Filologiczne, 2020)
Mark Humphries, Cities and the Meanings of Late Antiquity, Leiden–Boston: Brill, 2019 (Brill Research Perspectives), 112 pp., ISBN 978-90-04-42260-5 (e-book ISBN 978-90-04-42261-2), €70,00.